2023
DOI: 10.1002/chem.202203806
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Cooperative Reactivity at a Square Planar Aluminium Complex and Catalytic Reduction of CO2

Abstract: The use of a sterically demanding pincer ligand to prepare an unusual square planar aluminium complex is reported. Due to the constrained geometry imposed by the ligand scaffold, this four-coordinate aluminium centre remains Lewis acidic and reacts via differing metal-ligand cooperative pathways for activating ketones and CO 2 . It is also a rare example of a single-component aluminium system for the catalytic reduction of CO 2 to a methanol equivalent at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Like 4, the solid-state structure of 6 exhibits two bridging hydrides between aluminum and boron atoms, having a similar Al−B bond distance of 2.288(3) Å (Figure 5 Contrary to our expectation, the reaction of 1 with the more Lewis acidic B(C 6 F 5 ) 3 led to multiple rearranged products. One of the products, (2-Me 2 NCH 2 C 6 H 4 )Al(C 6 F 5 ) 2 (7), was crystallized from a mixture of toluene and n-pentane (Scheme 3 and Figure 6). X-ray diffraction studies on 7 showed that the aluminum center adopts the coordination number of 4, acquiring a tetrahedral geometry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like 4, the solid-state structure of 6 exhibits two bridging hydrides between aluminum and boron atoms, having a similar Al−B bond distance of 2.288(3) Å (Figure 5 Contrary to our expectation, the reaction of 1 with the more Lewis acidic B(C 6 F 5 ) 3 led to multiple rearranged products. One of the products, (2-Me 2 NCH 2 C 6 H 4 )Al(C 6 F 5 ) 2 (7), was crystallized from a mixture of toluene and n-pentane (Scheme 3 and Figure 6). X-ray diffraction studies on 7 showed that the aluminum center adopts the coordination number of 4, acquiring a tetrahedral geometry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Catalytic reduction of carbon dioxide (CO 2 ) is an attractive route for obtaining C 1 feedstock. As an alternative to transition metals, main-group elements were employed to prepare catalytically active compounds for CO 2 reduction to obtain formic acid, formaldehyde, methanol, and methane using dihydrogen (H 2 ), boranes, and silanes as hydrogen sources. Due to its abundance in the earth’s crust and low toxicity, aluminum is a potential metal for designing catalysts for CO 2 reduction. One of the earliest reports of CO 2 reduction to methanol by aluminum, using LiAlH 4 , appeared in 1948 . This inspired chemists to design molecular aluminum hydrides that could reduce CO 2 in a stoichiometric manner. With the advent of frustrated Lewis pairs (FLPs), the Mes 3 P­(AlX 3 ) system converted CO 2 to methanol using ammonia borane as a hydrogen source. ,, While stoichiometric reductions were successfully performed using aluminum compounds, , catalytic conversions are challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…σ-Bond metathesis is the rate-determining step in this catalytic cycle and is similarly rate-determining in many main-group hydride catalytic cycles . The use of main-group hydride catalysis has seen particular application in CO 2 valorization through hydrofunctionalization. …”
Section: Introductionmentioning
confidence: 99%